Wideband precision phase detection for magnetic induction spectroscopy. (February 2018) - Lyons, Samuel; Wei, Kent; Soleimani, Manuchehr
Abstract: Magnetic induction spectroscopy (MIS) has many potential applications in medical engineering as well as industrial and food manufacturing process applications, providing a contact-less impedance measurement. However, the applications of MIS is currently limited due to the high precision of phase detection required over a wide band of frequencies. This paper focuses on phase detection aspect of the MIS. The chosen phase detection method is investigated in depth and a prototype hardware and software is developed. The phase detection system is then tested and compared to other recent MIS system design. The prototype hardware is able to measure the phase difference of signals from 200 kHz to 20 MHz with milli-radian precision which will significantly enhance the MIS systems.